Incorporation of Zinc into Binary SiO2-CaO Mesoporous Bioactive Glass Nanoparticles Enhances Anti-Inflammatory and Osteogenic Activities - Haishui Sun; Kai Zheng; Tian Zhou; Aldo R. Boccaccini (MDPI AG, 2021)
During the healing and repair of bone defects, uncontrolled inflammatory responses can compromise bone regeneration. Biomaterials with anti-inflammatory activity are favorable for bone tissue regeneration processes. In this work, multifunctional Zn-containing mesoporous bioactive glass nanoparticles (Zn-MBGs) exhibiting favorable osteogenic and anti-inflammatory activities were produced employing a sol-gel method. Zn-MBGs exhibited a mesoporous spherical shape and nanoscale particle size (100 ± 20 nm). They were degradable in cell culture medium, and could release Si, Ca, and Zn in a sustained manner. Zn-MBGs also exhibited a concentration-dependent cellular response. The extract of Zn-MBGs obtained by incubation at 0.1 mg/mL (in culture medium) for 24 h could enhance in vitro mineralization, alkaline phosphatase activity, the expression of osteogenesis-related genes, and the production of intracellular protein osteocalcin of rat bone marrow stromal cells (BMSCs). Moreover, the extract of Zn-MBGs at 0.1 mg/mL could significantly downregulate the expression of inflammatory genes and the production of inducible nitric oxide in RAW 264.7 cells, particularly under stimulation of inflammatory signals interferon-γ (IFN-γ) and lipopolysaccharide (LPS). Zn-MBGs also inhibited the pro-inflammatory M1 polarization of RAW264.7 cells induced by LPS and IFN-γ. In summary, we successfully synthesized Zn-MBGs with concentration-dependent osteogenic and anti-inflammatory activities. Zn-MBGs show their great potential in immunomodulation strategies for bone regeneration, representing a multifunctional biomaterial that can be applied to regenerate bone defects under inflammatory conditions.